Sexualidad en la primaria, tratado de un inútil combate - Gamboa Barboza, Isabel (2010)
this paper proposes that girls and boys who went to Costa Rican primary schools after the 1960's have learnt that what is called “sexuality” refers to a mixture of obsessive concern towards reproduction and heterosexuality, and to meeting point for scientific rationality and a discourse of pleasure and sexual danger. It is also possible that these cultural impositions caused them feelings of inadequacy and distress. To do so, this paper analyzes textbooks, specially those of Sciences, published by the Ministry of Education since the 1960's to the present